Late-Term Abortion and Medical Necessity: A Failure of Science - James Studnicki (SAGE Publishing, 2019)
Roe V. Wade (1973) placed the concept of medical necessity at the center of the public discourse on abortion. Nearly a half century later, 2 laws dealing with late-term abortion, 1 passed in New York and 1 set aside in Virginia, are an indication that the medical necessity argument regarding abortion has been rendered irrelevant. More importantly for this discussion, these laws are an indication of the failure of the US scientific and medical communities to inform this consequential topic with transparency, logical coherence, and evidence-based objectivity.